2013
DOI: 10.1007/s40263-013-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hypothalamic H1 Receptor Antagonism in Antipsychotic-Induced Weight Gain

Abstract: Treatment with second generation antipsychotics (SGAs), notably olanzapine and clozapine, causes severe obesity side effects. Antagonism of histamine H1 receptors has been identified as a main cause of SGAinduced obesity, but the molecular mechanisms associated with this antagonism in different stages of SGAinduced weight gain remain unclear. This review aims to explore the potential role of hypothalamic histamine H1 receptors in different stages of SGA-induced weight gain/obesity and the molecular pathways re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 123 publications
(188 reference statements)
3
51
1
2
Order By: Relevance
“…Moreover, deprivation of food predominantly led to activation of H 1 R expression in the hypothalamic Arc [13,55]. It was confirmed that Intracerebroventricular (ICV) injection of the H 1 R agonist, 2-(3-trifluoromethylphenyl)histamine (FMPH) inhibited food intake [56].…”
Section: H 1 R H 3 R and Sga-induced Weight Gainmentioning
confidence: 86%
See 3 more Smart Citations
“…Moreover, deprivation of food predominantly led to activation of H 1 R expression in the hypothalamic Arc [13,55]. It was confirmed that Intracerebroventricular (ICV) injection of the H 1 R agonist, 2-(3-trifluoromethylphenyl)histamine (FMPH) inhibited food intake [56].…”
Section: H 1 R H 3 R and Sga-induced Weight Gainmentioning
confidence: 86%
“…Therefore, it is extremely important to prevent and treat weight gain/obesity induced by SGAs. It has been suggested that the histamine H 1 R, its downstream pathways and associated neuropeptide are involved in the SGA-induced weight gain/obesity side-effects [6,12,13]. It has been reported that betahistine acts as modulator for the histaminergic system through its H 1 R-agonsitic and H 3 R-antagonsitic properties in the brain [167,203].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The binding affinities of olanzapine to these neurotransmitter receptors are ranked in the following order: H 1 R>5-HT 2 R>D 2 R>αR and M 1 R (Uchida et al, 2007). Since a number of studies have shown that H 1 R plays a key role in olanzapine induced weight gain/obesity (Kim et al, 2007, Han et al, 2008a, He et al, 2013, H 1 R could be a therapeutic target for controlling olanzapine-induced weight gain side-effects. Recently we found in a rat model that olanzapine-induced weight gain can be partially reduced (-45%) by co-treatment with betahistine (an H 1 R agonist and H 3 R antagonist) .…”
Section: Introductionmentioning
confidence: 99%